The Impact of U.S. Economic Growthon the Rest of the World : How Much Does it Matter? - Vamvakidis, Athanasios; Arora, Vivek (Washington, D.C. : International Monetary Fund, 2001)
This paper provides a quantitative assessment of the impact of economic growth in the United States on growth in other countries. Using panel data estimation, the paper finds a significant positive impact of U.S. growth on growth in the rest of the world, especially developing countries, during the past few decades. The evidence suggests that the impact of U.S. growth on other countries can be explained by the significance of the United States as a global trading partner. The paper provides estimates of the direct impact of trade with the United States on growth in several individual countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet